2012
DOI: 10.1051/epjconf/20122900004
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Fe doping on properties of Pr0.67Ba0.33Mn1-xFexO3perovskites

Abstract: Abstract. Changes in the physical properties of ceramic Pr 0.67 Ba 0.33 Mn 1-x Fe x O 3 (0 ≤ x ≤ 0.15) are interpreted as resulting from the suppression of the ferromagnetic double exchange interaction with almost no lattice effect due to similar ionic radii value of Fe 3+ and Mn 3+ Magnetization and transport measurements show at low temperature ferromagnetic and metallic behavior for x=0 and 0.05 samples, whereas x = 0.10 and x = 0.15 compounds show spin glass like and semiconducting behavior. At high temper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2014
2014
2016
2016

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…The powders are pelleted at a pressure of 105 N cm À 2 .The samples are finally annealed at 1453 K for 24 h in air. In previous works [28,29], powder X-ray diffraction and powder neutron diffusion are used to investigate the structure and the morphology of the compound. They have shown that the structural parameters and the grain sizes are not affected by Fe doping.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The powders are pelleted at a pressure of 105 N cm À 2 .The samples are finally annealed at 1453 K for 24 h in air. In previous works [28,29], powder X-ray diffraction and powder neutron diffusion are used to investigate the structure and the morphology of the compound. They have shown that the structural parameters and the grain sizes are not affected by Fe doping.…”
Section: Methodsmentioning
confidence: 99%
“…On the other hand, the composition x¼ 0.1 represents the limit value of Fe concentration which destroys the metallic-insulator transition. Few works and less discussions have been done on the electrical properties of PrBaMnO 3 [27] and Fe doped PrBaMnO 3 [28,29]. In this work, we introduced iron in Pr 0.67 Ba 0.33 MnO 3 and we study its effect on the electrical properties of this compound.…”
Section: Introductionmentioning
confidence: 99%